Nanometer SiO2 / CTPBA / EP high-toughness adhesive and application
By using CTPBA and modified nano SiO2 in epoxy resin, combined with the modification treatment of silane coupling agent, the shortcomings of epoxy resin adhesive in terms of mechanics, bonding, thermodynamics and moisture resistance are solved, and high toughness and weather resistance are achieved. It is suitable for seawater pipeline repair and other applications.
Patent Information
- Application Number
- CN202410638221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-02-18
AI Technical Summary
The existing epoxy resin adhesives have shortcomings in mechanical properties, adhesive properties, thermodynamic properties and moisture resistance, especially in seawater pipeline repair applications, which are difficult to meet the requirements of high toughness and weather resistance.
The flexible segment-end carboxylic polyester CTPBA and modified nanoSiO2 were used in the epoxy resin and the nanoSiO2 was modified using the silane coupling agent KH-550 to form a high tough adhesive. This method enhances the mechanical properties and thermal stability of the adhesive by improving the dispersion and interaction of nano SiO2.
It significantly improves the tensile shear strength, tensile strength and impact strength of the adhesive, enhances its adhesive properties and thermodynamic properties, and optimizes moisture resistance, so that it can show higher toughness and Weather resistance.
Smart Images

Figure CN119463774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and in particular to a nano-SiO2 / CTPBA / EP high-toughness adhesive and application thereof. Background Art
[0002] In recent years, wet repair technology of composite materials has been often used for seawater pipeline repair. Among them, epoxy resin has the advantages of excellent mechanical properties, high bonding strength, low curing shrinkage, good corrosion resistance and low price. It is widely used in the preparation of adhesives, composite materials and coatings. However, pure epoxy resin cured products have defects such as poor toughness and low fracture energy, which limits its development in the field of advanced materials.
[0003] Toughening modification of epoxy resin can effectively improve its shortcomings such as high brittleness. Common methods include adding rubber elastomers, thermoplastic resins, inorganic nanoparticles and flexible segments. Toughening modification of rubber elastomers is to form block polymers, which form a two-phase structure during curing to improve the comprehensive mechanical properties of the material. However, it leads to a decrease in the heat resistance and glass transition temperature of the material. The modification of thermoplastic resins is mainly a crack-rivet mechanism, which can take into account both toughness and heat resistance, but the amount of thermoplastic resin used during modification is large, the solubility is poor, and the system viscosity is high, which has certain difficulties in the preparation process. Toughening of inorganic nanoparticles is mainly a crack deflection mechanism, but the poor dispersibility of nanoparticles makes it easy to agglomerate in the resin matrix, affecting the performance of the cured product. The mechanism of toughening epoxy resin with flexible segments is similar to that of toughening rubber elastomers, which can improve the toughness and impact resistance of epoxy resin, but it will also reduce the elastic modulus, mechanical strength and heat resistance, which limits its application in structural materials.
[0004] A single toughening method cannot meet the application requirements of epoxy resin in specific fields, while synergistically modified epoxy resin can achieve the goal of improving toughness and thermal properties. Linear polyester modified epoxy resin has achieved the improvement of toughness, impact strength and tensile shear strength, but it belongs to the "soft" flexible chain segment of the structure. The amount of flexible chain segment added needs to be strictly controlled during modification. When the amount added is too small, the toughening effect is not obvious, and when the amount added is too large, its tensile strength and heat resistance will be lost. Introducing another modifier for synergistic toughening is a feasible way. The composite material formed in this way can not only inherit a series of advantages of polymers, but also has the advantages of reinforcing phases. It has been widely used in flame retardant, anti-corrosion and electromagnetic fields.
[0005] Nanomaterials are good epoxy resin modified fillers and can be considered as synergistic modifiers. One type is planar nanomaterials, such as graphene and its derivatives, boron nitride, molybdenum disulfide, etc., which mainly provide good physical shielding effects through planar molecular structures and improve the anti-corrosion properties of epoxy resin coatings; the other type is nanoparticle materials, such as TiO2, Al2O3, SiO2, ZnO, CaCO3, etc., which can significantly improve the mechanical properties, anti-corrosion properties, weather resistance and other special properties of epoxy resins. Al2O3 can greatly improve the bending strength and impact strength of epoxy resins, and reduce its friction coefficient and wear rate. TiO2 can improve the shear properties of epoxy resins, improve the mechanical properties, but reduce the toughness. CaCO3 powder materials can be ultra-fine, and the crystal structure and surface electronic structure have special size effects and surface effects, which can effectively improve the impact strength and tensile strength of epoxy resins. ZnO is often used to enhance the corrosion resistance of epoxy resin coatings, which can effectively improve the surface micro-roughness of the coating and increase the water contact angle. The advantages of nano-SiO2 are large specific surface area, small particle size, and good thixotropy. It can effectively improve the interfacial adhesion and toughness of epoxy resin adhesives, improve the thermal stability of its cured products, and change the glass transition temperature of the material. This characteristic can expand its application in the field of adhesives. Nano-SiO2 has a three-dimensional chain structure and contains unsaturated bonds and hydroxyl groups in different bonding states. In addition to being able to undergo grafting and bonding with some groups in epoxy resin, it is also easy to modify nano-SiO2 through chemical reactions, which can improve the compatibility and dispersibility of nano-SiO2 in the resin matrix, thereby effectively realizing the coordinated modification of the material and avoiding the "agglomeration" phenomenon of nano-particles, which causes some defects in the cross-linked network structure of the material. When subjected to external forces, it is easy to develop into cracks due to stress concentration, which reduces the impact toughness. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a nano-SiO2 / CTPBA / EP high-toughness adhesive and its application to overcome the deficiencies in the above-mentioned prior art.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: a nano-SiO2 / CTPBA / EP high-toughness adhesive, comprising: a CTPBA / EP resin matrix, and nano-SiO2 modified by a silane coupling agent and mixed therein.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the dosage of nano-SiO2 is 1 to 5 phr.
[0010] Furthermore, the amount of CTPBA in the CTPBA / EP resin matrix is 20 phr, and the amount of EP resin is 100 phr.
[0011] Further, the method of modifying nano-SiO2 with a silane coupling agent is as follows:
[0012] 1) Pretreatment: Place the nano-SiO2 in a 120°C oven for 1 day and then take it out for use;
[0013] 2) Hydrolysis of silane coupling agent: Weigh 5% of the mass of nano-SiO2 silane coupling agent KH-550, add appropriate amount of deionized water to prepare a 5% aqueous solution, adjust the pH to 4-7, and place in an ultrasonic cleaning instrument for oscillation to fully hydrolyze the silane coupling agent;
[0014] 3) Dispersing nano-SiO2: Adding nano-SiO2 into an ethanol solution to prepare an ethanol solution with a mass concentration of 5 wt.%, and placing it in an ultrasonic cleaning apparatus for oscillation to make the nano-SiO2 evenly mixed in the ethanol solution;
[0015] 4) Modification of nano-SiO2: Add the hydrolyzed silane coupling agent solution to the nano-SiO2 / ethanol solution, place in a magnetic stirrer for modification, the temperature is 70°C, and the reaction is stopped after magnetic stirring for 2 hours;
[0016] 5) Drying: Filter the modified nano-SiO2 and wash it with anhydrous ethanol to remove the residual silane coupling agent. Wash it several times, dry it in an oven at 120°C, and grind it to obtain the modified nano-SiO2.
[0017] Furthermore, the EP resin is bisphenol A epoxy resin with an epoxy value of 0.48 to 0.52.
[0018] Furthermore, the nano-SiO2 / CTPBA / EP high-toughness adhesive also includes a curing agent, and the amount of the curing agent is 25 phr.
[0019] Furthermore, the curing agent is phenalkamine T-31.
[0020] Furthermore, the preparation method of nano-SiO2 / CTPBA / EP high-toughness adhesive is as follows: add nano-SiO2 modified by silane coupling agent into CTPBA / EP resin matrix, stir, ultrasonically vibrate, add curing agent, mix well and then vacuum degas.
[0021] Furthermore, the stirring time was 15 min and the ultrasonic oscillation time was 30 min.
[0022] Based on the above technical solution, the present invention also provides a nano-SiO2 / CTPBA / EP high-toughness adhesive for use in seawater pipeline repair.
[0023] The beneficial effects of the present invention are:
[0024] The epoxy resin is toughened and modified by the flexible segment end carboxyl polyester CTPBA and modified nano-SiO2, avoiding the characteristics of the flexible segment modification that easily loses its tensile strength and heat resistance. Considering the characteristic that nano-SiO2 is easy to "agglomerate", the silane coupling agent KH550 is selected to modify the nano-SiO2, reduce the surface free energy of nano-SiO2, enhance its lipophilicity, effectively improve the dispersion of nano-SiO2 in the resin matrix, and enhance the interaction between nano-SiO2 and the resin matrix, so as to achieve the effect of effective synergistic modification, and achieve a significant improvement effect on the mechanical properties, bonding properties, thermodynamic properties and moisture resistance of the adhesive. Among them, the adhesive The tensile shear strength, tensile strength and impact strength of the adhesive first increase and then decrease with the increase of the amount of modified nano-SiO2 added, reaching the maximum value at 2phr, which are 6.96%, 56.62% and 68.22% higher than those without addition, respectively. SEM impact cross-sectional morphology analysis shows that the toughening mechanism is the shear deformation caused by CTPBA and the second phase toughening caused by nano-SiO2. The addition of nano-SiO2 can shorten the gel time, improve the peel strength and heat resistance of the system, and reduce the glass transition temperature. The water absorption rate of the adhesive first decreases and then increases with the increase of the amount of modified nano-SiO2 added, reaching the minimum value at 2phr, and the moisture resistance is optimal. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the schematic diagram of the hydrolysis reaction of KH-550 and its reaction with SiO2;
[0026] Figure 2 The flow chart for the preparation of nano-SiO2 / CTPBA / EP high-toughness adhesive;
[0027] Figure 3 Spectral analysis of nano-SiO2 before and after modification, (a) infrared spectrum, (b) UV-visible spectrum;
[0028] Figure 4 Thermogravimetric images before and after nano-SiO2 modification;
[0029] Figure 5 SEM of nano-SiO2, (a) before modification; (b) after KH-550 modification;
[0030] Figure 6 The contact angle after nano-SiO2 modification, (a) before modification, (b) after modification;
[0031] Figure 7 This is the influence curve of SiO2 addition on the tensile shear strength of CTPBA / EP epoxy resin adhesive;
[0032] Figure 8This is the effect curve of SiO2 addition on the gel time of CTPBA / EP epoxy resin adhesive;
[0033] Fig. 9 This is the effect curve of SiO2 addition on the peel strength of CTPBA / EP epoxy resin adhesive;
[0034] Fig.10 This is the effect curve of SiO2 addition on the tensile strength and elongation at break of CTPBA / EP epoxy resin adhesive;
[0035] Fig.11 This is the influence curve of SiO2 addition on the impact strength of CTPBA / EP epoxy resin adhesive;
[0036] Fig.12 SEM images of SiO2 modified CTPBA / EP epoxy resin at (a) 0phr; (b) 1phr; (c) 2phr; (d) 3phr; (e) 4phr; (f) 5phr.
[0037] Fig.13 (a) TG curve, (b) DTG curve;
[0038] Fig.14 Nano-SiO2 modified epoxy resin adhesive, (a) tanδ-T curve; (b) storage modulus E curve;
[0039] Fig.15 This is a graph showing the change in water absorption of nano-SiO2 with different contents. DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0041] Bisphenol A epoxy resin E-51 was used as the research object, phenolic amine T-31 was used as the curing agent, and carboxyl-terminated polybutylene adipate (CTPBA) was used as the toughening agent (self-made in the laboratory, the addition amount was 20phr, phr represents the addition amount required for every 100 parts of E-51, and phr in this paper is based on this standard. The preparation method of E-CTPBA can be found in the literature [LUO X, LI Y, SUN ZY, et al. Preparation and research of epoxy modified by carboxyl-terminated polybutylene adipate at room temperature [J]. RSC Advances, 2022, 12: 20471-20480.]) Nano-SiO2 modified with silane coupling agent (KH-550) was used as an inorganic nanofiller. The effect of the amount of modified nano-SiO2 added on the mechanical properties, bonding properties, thermodynamic properties and moisture resistance of the CTPBA / EP (carboxyl-terminated polybutylene adipate / epoxy resin) composite material system was systematically studied. The synergistic toughening mechanism of KH-550 modified nano-SiO2 and CTPBA was studied and discussed, revealing the synergistic effect of improving the mechanical properties of the material.
[0042] Experimental materials:
[0043] Bisphenol A epoxy resin (E-51): industrial grade, epoxy value 0.48-0.52, Nantong Xingchen Synthetic Materials Co., Ltd.
[0044] Adipic acid: analytical grade, Tianjin Kemeiou Chemical Reagent Co., Ltd.;
[0045] 1,4-Butanediol: analytical grade, Xilong Scientific Co., Ltd.;
[0046] Triphenylphosphine: analytical grade, Aladdin Reagent (Shanghai) Co., Ltd.;
[0047] T-31 curing agent: industrial grade, amine value 520mg / KOH / g, Guangzhou Yueqiang Chemical Co., Ltd.
[0048] Anhydrous ethanol: analytical grade, Sinopharm Chemical Reagent Co., Ltd.;
[0049] p-Toluenesulfonic acid: analytical grade, Tianjin Damao Chemical Reagent Factory;
[0050] Degussa fumed nanosilica A380 (SiO2): specific surface area 380±30m / g, average primary particle size 7nm;
[0051] Silane coupling agent KH-550: content ≥99%, Kangjin New Material Technology Co., Ltd.
[0052] The modification method of nano-SiO2 is as follows:
[0053] The silane coupling agent KH-550 is used to modify the nano-SiO2. The working principle is as follows: Figure 1 The specific operations are as follows:
[0054] 1) Pretreatment: Place the nano-SiO2 in a 120°C oven for 1 day and then take it out for use;
[0055] 2) Hydrolysis of silane coupling agent: Weigh 5wt.% (5% of the mass of nano-SiO2) of silane coupling agent KH-550, add appropriate amount of deionized water to prepare an aqueous solution with a mass concentration of 5%, adjust the pH to 4-7 to accelerate hydrolysis, place in an ultrasonic cleaner and oscillate for 20 minutes to fully hydrolyze the silane coupling agent;
[0056] 3) Dispersing nano-SiO2: adding measured nano-SiO2 into an ethanol solution to prepare an ethanol solution with a mass concentration of 5wt.%, placing it in an ultrasonic cleaning instrument and oscillating it for 15 minutes to make the nano-SiO2 evenly mixed in the ethanol solution;
[0057] 4) Modification of nano-SiO2: Add the hydrolyzed silane coupling agent solution to the nano-SiO2 / ethanol solution, place in a magnetic stirrer for modification, the temperature is 70°C, and the reaction is stopped after magnetic stirring for 2 hours;
[0058] 5) Drying: Filter the modified nano-SiO2 and wash it with anhydrous ethanol to remove the residual silane coupling agent. Repeat the washing 5 times, dry it in an oven at 120°C, grind it and set it aside.
[0059] Preparation of SiO2 / CTPBA / EP adhesive:
[0060] The modified nano-SiO2 was added into CTPBA / EP resin matrix (CTPBA / EP, 20phr / 100phr) at 0phr, 1phr, 2phr, 3phr, 4phr and 5phr, respectively, stirred for 15min with a high-speed stirrer and ultrasonically vibrated for 30min, and then used as component A;
[0061] T-31 curing agent is used at 25phr as component B;
[0062] The two components are mixed and vacuum degassed after being fully mixed. The sample is prepared. The preparation process of SiO2 / CTPBA / EP adhesive is as follows: Figure 2 The formula design is shown in Table 1:
[0063] Table 1 SiO2 / CTPBA / EP adhesive formulation
[0064]
[0065] The tensile properties test was carried out according to GB / T 2567-2008, at 25°C and a test speed of 10 mm / min.
[0066] The impact performance test refers to GB / T 2567-2008, and the notchless impact method is selected. The plastic pendulum impact tester (PTM1000) is used for the test, and the sample size is 120mm×15mm×10mm;
[0067] The tensile shear strength test refers to GB / T 7124-2008. A 100mm×25mm×1.6mm SUS321 stainless steel sheet is selected. After grinding, the surface is cleaned with acetone, washed and dried for use. The bonding surface length is 12.5±0.25mm, the width is 25±0.25mm, the adhesive layer thickness is about 0.2mm, and the overflow is cleaned in time. After curing for 2 days, the test is carried out at 25°C using a universal tensile testing machine with a test speed of 2mm / min.
[0068] The T-peel strength test refers to GB / T 2791-1995. The flexible material is stainless steel, with a length of 200 mm, a width of 25 mm, a thickness of 0.15 mm, a coating length of 150 mm, and peeling at 100 mm / min.
[0069] The gel time test refers to GB / T 16995-1997. Add measured modified epoxy resin and curing agent into a plastic cup, stir quickly and start timing. When the viscosity increases, stop stirring and start drawing wires. When the wires become brittle and break and cannot be drawn into wires, stop timing.
[0070] Fourier transform infrared spectrometer (FT-IR, Thermo Scientific, Nicolet iS20) was used to characterize the nano-SiO2 before and after modification, with a scanning range of 4000 cm -1 ~400cm -1 , resolution 4cm -1 , scan times 32 times.
[0071] The UV-visible spectrum test adopts the method in the reference [HE Shuting, LIU Baochun. Surface modification of nano-SiO2[J]. Applied Chemical Industry, 2017, 46(04): 693-697. HE Shuting, LIU Baochun. Surface modification of nano-SiO2[J]. Applied Chemical Industry, 2017, 46(04): 693-697.], and the higher the UV absorbance, the better the dispersibility. Weigh 0.1g of the sample modified by silane coupling agent in 10mL ethanol solution, ultrasonically disperse for 30min and then stand for 24h. Select the upper suspension dispersion and use UV-6000PC UV-visible spectrophotometer for testing. The test range is 200nm~800nm.
[0072] The contact angle of nano-SiO2 before and after modification was tested using a contact angle meter SDC-80. The test solution was deionized water. The test method adopted the static drop method, with a dosage of 3 μL each time.
[0073] Refer to GB / T 1034-2008 test method for determination of water absorption of plastics, the sample size is 10mm×10mm×1mm, the sample is placed in a 104℃ oven for 1h, and after weighing, it is immersed in 23℃ distilled water, and the mass before immersion W0 is weighed with a precision electronic balance within 1min (accurate to 0.0001g). After immersion for 24h, take out the sample, quickly wipe off the water on the surface of the sample with filter paper, and weigh the mass after immersion W1 (accurate to 0.0001g), and the weighing is also completed within 1min. Similarly, the mass after immersion for t days is Wt, and the water absorption mass fraction after immersion for t days is calculated according to the formula:
[0074]
[0075] Where C t ——mass fraction of water absorbed by the sample (%), W0——initial mass before immersion (g); W t ——Mass of sample after immersion (g).
[0076] The thermal stability of the modified epoxy resin cured product was tested using a HT / 1600 thermogravimetric analyzer. 5 to 10 mg of the sample was weighed in a crucible. The temperature was raised in the range of 25 to 700°C, the heating rate was 10°C / min, and the gas atmosphere was N2.
[0077] The glass transition temperature of the sample was tested using a dynamic mechanical analyzer (DMA, Mettler Toledo) in a single cantilever measurement mode, a heating rate of 3°C / min, a temperature range of 25-150°C, and a test frequency of 1 Hz.
[0078] The Czech TESCAN MIRALMS scanning electron microscope was used to test the morphology of nano-silicon dioxide and the impact fracture surface of the solidified material. After the fracture surface was gold-plated, the acceleration voltage was 15keV.
[0079] 1) Property analysis of nano-SiO2 before and after modification
[0080] In order to determine whether the nano-SiO2 powder has been modified, the nano-SiO2 powder before and after modification was subjected to the following experimental analysis:
[0081] 1.1.1 Infrared spectroscopy analysis
[0082] Test results such as Figure 3 As shown in (a), nano-SiO2 has multiple characteristic absorption peaks, among which 467.72 cm -1 、809.44cm -1 and 1099.07cm -1 They are the bending vibration peak, symmetric stretching vibration peak and antisymmetric stretching vibration peak of Si-O-Si bond, 3432.75cm -1 The peak at 2900cm is the stretching vibration peak of hydroxyl group. The absorption peak intensity is reduced after modification relative to Si-O-Si bond, indicating that the reaction point between nano-SiO2 and silane coupling agent is on the hydroxyl group of nano-SiO2. The infrared spectrum of modified nano-SiO2 is at 2900cm -1 ~3000cm -1 The characteristic absorption peaks of methyl and methylene stretching vibration appeared, indicating that the silane coupling agent was successfully grafted onto the SiO2 surface.
[0083] 1.1.2 UV spectrum analysis
[0084] The results of UV-visible absorption spectroscopy on the dispersion of the solution are as follows: Figure 3 As shown in (b), the UV absorption of modified nano-SiO2 in the range of 200-500nm is higher than that of unmodified nano-SiO2. It is speculated that the hydrophobicity of modified nano-SiO2 is increased (this point of view is proved in the contact angle analysis later), making it easier to disperse in anhydrous ethanol. Therefore, the suspension has a higher UV absorption rate, indicating that KH-550 successfully modified nano-SiO2.
[0085] 1.1.3 Thermogravimetric analysis
[0086] Figure 4This is the thermogravimetric curve of nano-SiO2 before and after modification in N2 atmosphere. The unmodified nano-SiO2 has good thermal stability. Only the large number of hydroxyl groups on its surface will cause it to lose a small amount of weight at the beginning. The weight loss rate is 1.59% at 700°C. The mass loss of nano-SiO2 modified with KH-550 is more obvious, with a weight loss rate of 6.98% at 700°C. It is speculated that this is the decomposition of the amino group and carbon chain of KH-550, indicating that KH-550 has successfully modified the SiO2 surface.
[0087] 1.1.4SEM characterization
[0088] In order to compare the effect of silane coupling agent KH-550 on the morphological structure of nano-SiO2, the surface morphology of nano-SiO2 before and after modification was characterized by scanning electron microscopy (SEM). Figure 5 As shown in the figure, due to the small size of nanoparticles, it is difficult to disperse evenly. It is observed that the nano-SiO2 is obviously agglomerated before modification and is in the form of amorphous white particles. This is due to its large surface area and high surface energy. After modification, it is found that its dispersibility is significantly improved and the particle size is smaller. It is speculated that the silane coupling agent is attached to its surface, which reduces the surface energy and improves the dispersibility.
[0089] 1.1.5 Contact angle analysis
[0090] The change in contact angle is an important criterion for judging whether the modification is successful or not. Figure 6 It is the contact angle of nano-SiO2 before and after modification. As can be seen from the figure, the contact angle of unmodified nano-SiO2 is 76.9°, while the contact angle of KH-550 modified nano-SiO2 is 103°. It can be seen that the lipophilicity of nano-SiO2 modified by KH-550 is enhanced.
[0091] Through comparative analysis, it can be inferred that the silane coupling agent contains polar groups and non-polar groups. The polar groups are easy to react with the large number of hydroxyl groups contained in nano-SiO2 and thus grafted on the surface of the filler, while the other end is a non-polar group, which is wrapped on the surface of nano-SiO2, thereby increasing the hydrophobicity and improving the compatibility with the epoxy resin matrix.
[0092] 1.2 Effect of coupling agent on the performance of epoxy resin adhesive
[0093] Table 2 Effect of coupling agent on CTPBA / EP epoxy resin adhesive
[0094]
[0095]
[0096] In this experiment, the fillers are unmodified nano-SiO2 and KH-550 modified nano-SiO2, and the addition amount is 2phr. The experimental results of tensile shear strength, tensile strength, elongation at break, impact strength and hardness of filler-modified epoxy resin adhesive are shown in Table 2. It can be seen that the unmodified nano-SiO2 reduces the mechanical properties and bonding properties of epoxy resin, while the nano-SiO2 modified by KH-550 greatly improves the mechanical properties of the adhesive. According to the previous characterization of nano-SiO2, it can be inferred that the unmodified nano-SiO2 has poor compatibility with organic matter, is not easy to diffuse and "agglomerate" in the resin matrix, and a large number of defects will appear in the curing process, which reduces the comprehensive mechanical properties of the material. After modification by silane coupling agent, it can be coupled with the resin matrix, so that the tendency of nanoparticles to agglomerate is suppressed, its surface energy is reduced, the interfacial bonding strength is increased, and the compatibility between the two is improved, so that the mechanical properties of the adhesive are effectively improved.
[0097] 2. Effect of modified nano-SiO2 on the bonding properties of CTPBA / EP adhesive
[0098] 2.1 Effect on the tensile shear strength of CTPBA / EP adhesive
[0099] like Figure 7 As shown in the figure, the addition of modified nano-SiO2 significantly improves the tensile shear strength of the material. When the addition amount of modified nano-SiO2 is 2phr, the tensile shear strength of SiO2 / CTPBA / EP reaches a maximum value of 12.14MPa, which is 6.96% higher than that without addition. The surface of nano-SiO2 is extremely active, and the appropriate amount of addition can ensure good dispersion. In addition, after modification by coupling agent, it is easy to bond with the epoxy resin matrix to form a cross-linked network structure, which makes the interface bonding strength higher. When subjected to external force, SiO2 can disperse stress. The existence of interface effect improves the bonding strength. When the addition amount continues to increase, the nanoparticles may "agglomerate" due to excessive dispersion, resulting in poor dispersion, and stress concentration at the SiO2 / CTPBA / EP resin interface, resulting in a decrease in tensile shear strength.
[0100] 2.2 Effect on gel time of CTPBA / EP adhesive
[0101] like Figure 8 As shown in the figure, the gel time of CTPBA / EP adhesive gradually decreases with the increase of nano-SiO2, and the curing speed gradually accelerates. Nano-SiO2 has a large specific surface area and many surface hydroxyl groups, which are easy to bond with the resin matrix. The active amino groups introduced after modification with KH-550 can also react with the epoxy resin. Therefore, the increase in the added amount increases the active sites and accelerates the curing reaction speed.
[0102] 2.3 Effect on the peel strength of CTPBA / EP adhesive
[0103] like Fig. 9 As shown in the figure, after adding KH-550 to modify nano-SiO2, the peel strength decreases, and then increases with the increase of the addition amount. When the addition amount is 5phr, it is 72% higher than the pure resin matrix. This may be because the compatibility of nano-SiO2 with the resin matrix is enhanced after modification by silane coupling agent, and the nanoparticles have a large specific surface area and can form an interfacial bonding with the epoxy resin, which effectively improves the strength, toughness and ductility of the material. At the same time, the addition of nanoparticles will affect the proportion of raw materials, and the two work together to determine the size of the peel strength.
[0104] 3. Effect of modified nano-SiO2 on mechanical properties of CTPBA / EP adhesive
[0105] 3.1 Effect on tensile strength and elongation at break of CTPBA / EP adhesive
[0106] Effect of modified nano-SiO2 addition on the tensile strength and elongation at break of CTPBA / EP epoxy resin Fig.10 As shown in the figure, with the increase of SiO2 addition, the tensile strength is significantly enhanced, reaching a maximum value of 48.02MPa when the addition amount is 2phr, which is 56.62% higher than that without SiO2 addition. As the addition amount continues to increase, the tensile strength begins to decrease, but it is still higher than the tensile strength without SiO2 addition. The elongation at break drops sharply after adding SiO2, and shows a trend of first increasing and then decreasing when the addition amount is 1-5phr. It reaches a maximum value of 2.62% when the addition amount is 2phr, which is 31.66% higher than that of 1phr.
[0107] It is speculated that after being modified with KH-550, nano-SiO2 can form a good interface connection with the resin matrix. When subjected to tension, the stress can be well dispersed through the interface. In addition, the nanoparticles themselves are relatively strong, and it takes more energy to break. Due to their good adhesion to the resin, they can prevent the expansion of microcracks when the material is under stress, so that it requires greater stress to pull it out of the resin matrix. Macroscopically, it manifests as an enhancement of tensile strength, the so-called silver streak-rivet mechanism. The addition of nano-SiO2 reduces the spatial distance between the cross-linked chains to below the critical length, which reduces the fracture performance, manifested as a significant decrease in the elongation at break. When the addition amount is too much, the nanoparticles may be too dense and easy to agglomerate, and the tensile strength and elongation at break are reduced due to stress concentration.
[0108] 3.2 Effect on the impact strength of CTPBA / EP adhesive
[0109] Effect of modified nano-SiO2 addition on the impact strength of CTPBA / EP adhesive Fig.11 As shown in the figure, it can be seen that the appropriate addition of fillers can effectively improve the impact strength of the material, and with the increase of the added amount, the impact strength begins to increase. When the added amount is 2phr, it reaches a maximum value of 6.25, which is 68.22% higher than that without SiO2 addition, and the improvement rate is about 18% higher than that of unmodified SiO2. This may be because when the amount of nanoparticles added is small, they can be more evenly dispersed in the resin matrix, and the contact surface area with the epoxy resin is larger, which can improve the interface bonding between the nanoparticles and the resin matrix. At the same time, when impacted, the nanoparticles can absorb a certain amount of energy, hinder the expansion of resin cracks and prevent them from developing into destructive fractures, thereby achieving the purpose of toughening.
[0110] Continuing to increase the amount of filler may cause agglomeration due to excessive filler content, resulting in more interface defects. When subjected to external force, stress concentration is likely to occur, resulting in a decrease in impact strength. This can be verified by taking SEM photos of the impact section of the above sample, such as Fig.12 As shown in the figure, when the addition amount of nano-SiO2 is low (Figure b and Figure c), a large number of shear deformation, voids and crack deflection and termination can be observed. Among them, the shear deformation can absorb part of the impact energy and improve the toughness. The formation of voids is due to the de-embedding behavior of nano-SiO2 in the matrix. When the sample is subjected to impact, some nano-SiO2 particles peel off from the resin matrix and absorb a certain amount of impact energy, which effectively improves its impact toughness. At the same time, it can be observed that the nano-SiO2 particles are evenly distributed in the resin matrix, and there are relatively few particles exposed, indicating that the compatibility with the resin matrix is better at this time, and some particles are located at the crack tip, which plays a pinning effect, effectively inhibits the transmission of the crack, and improves the toughness. When the addition amount is 2phr, the nanoparticles are dispersed more evenly, the fracture surface is rougher, the ductile fracture is more obvious, and the fracture requires more energy, thereby achieving the improvement of mechanical properties. Another literature [SINGH SK, SINGH S, KUMAR A, et al. Thermomechanical behavior of TiO2 dispersed epoxy composites [J]. Engineering Fracture Mechanics, 2017, 184: 241-248.] reported that the addition of nanoparticles can reduce the length of the silver bar and produce a rougher fracture surface.
[0111] When the addition amount of nano-SiO2 continues to increase, a large number of "agglomerated" particles exposed outside can be observed, and the "agglomeration" becomes more obvious with the increase of the addition amount, thereby reducing the impact strength. The above SEM photos of the impact section of nano-SiO2 modified CTPBA / EP epoxy resin adhesive show that the toughening mechanism of nano-SiO2 toughened modified CTPBA / EP epoxy resin adhesive is the shear deformation mechanism caused by the flexible chain segment CTPBA and the second phase toughening mechanism induced by nano-SiO2, which play a synergistic toughening role.
[0112] 4. Material thermal stability analysis
[0113] The thermal stability of a material can usually be expressed as the weight loss temperature T d and the maximum thermal degradation rate temperature T max To evaluate, Fig.13 Table 3 is the thermogravimetric (TG) curve and DTG curve of pure CTPBA / EP resin matrix and CTPBA / EP matrix modified with nano-SiO2 under N2 atmosphere. Table 4 is the thermal degradation parameters of SiO2 modified CTPBA / EP composite materials:
[0114] Table 3 shows the thermal degradation parameters of SiO2 modified CTPBA / EP composites
[0115]
[0116] from Fig.13 As can be seen from (a), the thermal weight loss process of the resin modified by adding nano-SiO2 is similar to that of the resin matrix without adding nano-SiO2 in N2 atmosphere. The addition of nano-fillers significantly improves the thermal stability of the CTPBA / EP resin matrix. T5 is 9.35℃ higher than that of the resin matrix, and the residual carbon rate is 4.15% higher than that of the resin. This may be because nano-SiO2 itself is an inorganic nanoparticle with good thermal stability. After being added to the system, it forms a strong interaction with the CTPBA / EP resin matrix, making it require higher energy to break, resulting in improved thermal stability. Fig.13(b) is the DTG curve of different added amounts of nano-SiO2. It can be seen from the figure that the DTG curve of the CTPBA / EP resin matrix has two peaks, which means that the decomposition of the resin matrix is divided into two steps, namely the thermal decomposition of the resin matrix and the oxidation of cracking residual carbon. The addition of modified nano-SiO2 makes the second peak flatter, and the temperature Tmax corresponding to the maximum thermal weight loss rate moves toward the high temperature direction. On the one hand, this may be because the nano-SiO2 modified by the silane coupling agent is easy to bond with the resin matrix to form a cross-linked network structure, which makes the "firmness" of the resin matrix greater, thereby improving the thermal stability of the CTPBA / EP epoxy resin; on the other hand, the fully dispersed nanoparticles limit the movement of the chain segments and form internal winding channels in the resin matrix. During the decomposition process, the channels hinder the volatilization of the decomposition products, which effectively improves the thermal stability.
[0117] 5. Dynamic Mechanical Analysis (DMA)
[0118] Fig.14 (b) is the storage modulus variation curve of SiO2 / CTPBA / EP epoxy resin adhesive with temperature. As shown in the figure, when 2phr modified nano-SiO2 is added, the storage modulus of the material increases, which is consistent with the report in the literature [SONG Binhong, SHI Yuying, MO Jianghua, et al. Research on the application of gas-phase nano-silica to improve the bonding process of EP adhesive [J]. China Adhesives, 2016, 25(01): 13-15.]. This may be because nanoparticles can enhance the stiffness of the resin matrix. This enhancement makes the stress transfer at the interface higher. The storage modulus decreases with increasing temperature, especially near the glass transition temperature Tg, where the storage modulus decreases fastest because the molecular chain segments move faster and the fluidity increases.
[0119] Fig.14(a) is the tanδ-T curve of pure CTPBA / EP resin matrix and nano-SiO2 modified epoxy resin composite material. As can be seen from the figure, in the test temperature range of 25-150℃, the composite material has only one tanδ peak, corresponding to only one glass transition temperature, indicating that the system of nano-SiO2 modified epoxy resin is a thermodynamically compatible solidified material. Compared with the CTPBA / EP resin matrix without adding nano-SiO2, the Tg of the composite material with modified nano-SiO2 moves towards the low temperature direction. At present, there is no clear concept of the effect of nano-SiO2 addition on the glass transition temperature, and the research results are also very different. With the increase of SiO2 addition, Tg increases, decreases, has no obvious change, and is nonlinear.
[0120] Table 4 Damping parameters of nano-SiO2 with different addition amounts
[0121] content Tg(℃) tanδmax 0phr 70.3 0.78 2phr 57.7 1.03
[0122] Regarding the reason for the decrease in Tg, the literature [Preghenella M, Pegoretti A, Migliaresi C. Thermomechanical characterization of fumed silica-epoxy nanocomposites [J]. Polymer, 2005, 46 (26): 12065-12072] believes that the addition of nanoparticles increases the viscosity of the system sharply, reduces the degree of curing reaction, and thus reduces the crosslinking density of the system, which reduces Tg. When the amount of nanoparticles added is increased again, the movement of the chain segments is hindered, which correspondingly leads to an increase in Tg, but it is still lower than the Tg of the resin matrix.
[0123] 6. Water resistance
[0124] The water resistance of epoxy resin adhesive is also an important indicator in its actual engineering application process. The influence of different addition amounts of nano-SiO2 modified CTPBA / EP resin adhesive on water absorption is shown in Figure 2. Fig.15As shown in the figure, it can be seen that the water absorption of modified CTPBA / EP shows a trend of first decreasing and then increasing with the increase of the addition amount of KH-550 modified nano-SiO2; when the addition amount is 2phr, the water absorption of the adhesive reaches the minimum value of 0.05%, indicating that the silane coupling agent modified nano-SiO2 can effectively improve the moisture resistance of CTPBA / EP, and the optimal addition amount is 2phr. This may be due to the fact that the modified nano-SiO2 can be evenly dispersed in the resin matrix, and its specific surface area is large, and the contact surface area with the epoxy resin is large. The interface bonding between the nanoparticles and the resin matrix can be improved through the action of the silane coupling agent, and the formed network structure can effectively resist the penetration of water molecules. When the amount of nano-SiO2 added is too much, the agglomeration produces cavities that are easy to penetrate water molecules, making the water resistance worse.
[0125] In this scheme, the purpose is to toughen the brittle epoxy resin. The epoxy resin is toughened and modified by the flexible segment end carboxyl polyester CTPBA and modified nano-SiO2, avoiding the characteristics of the flexible segment modification that easily loses its tensile strength and heat resistance. Considering the characteristic that nano-SiO2 is easy to "agglomerate", the silane coupling agent KH-550 is selected to modify the nano-SiO2, reduce the surface free energy of nano-SiO2, enhance its lipophilicity, effectively improve the dispersion of nano-SiO2 in the resin matrix, and enhance the interaction between nano-SiO2 and the resin matrix, so as to achieve an effective synergistic modification effect, and significantly improve the mechanical properties, bonding properties, thermodynamic properties and moisture resistance of the adhesive. The tensile shear strength, tensile strength and impact strength of the adhesive increased first and then decreased with the increase of the amount of modified nano-SiO2 added, reaching the maximum value at 2phr, which was 6.96%, 56.62% and 68.22% higher than that without addition, respectively. The SEM impact section morphology analysis showed that the toughening mechanism was the shear deformation caused by CTPBA and the second phase toughening caused by nano-SiO2. The addition of nano-SiO2 could shorten the gel time, improve the peel strength and heat resistance of the system, and reduce the glass transition temperature. The water absorption of the adhesive decreased first and then increased with the increase of the amount of modified nano-SiO2 added, reaching the minimum value at 2phr, and the moisture resistance was the best.
[0126] The conclusion is as follows:
[0127] 1) The comprehensive mechanical properties of the nano-SiO2 modified resin system treated with silane coupling agent are significantly better than those of the untreated nano-SiO2 modified resin system and the original single toughening system;
[0128] 2) The addition of modified nano-SiO2 improves the bonding performance of the CTPBA / EP resin system. When the addition amount of nano-SiO2 is 2phr, the tensile shear strength is the largest. Nano-SiO2 can accelerate the curing speed, and the gel time decreases with the increase of the addition amount. When the addition amount of nano-SiO2 is in the range of 1 to 5phr, the peel strength increases with the increase of the addition amount.
[0129] 3) The addition of modified nano-SiO2 significantly improved the comprehensive mechanical properties of the CTPBA / EP resin system. When the addition amount of nano-SiO2 was 2phr, the tensile strength and impact strength were the highest, while the addition of modified nano-SiO2 decreased the elongation at break. However, when the addition amount was in the range of 1-5phr, it showed a trend of first increasing and then decreasing, reaching the maximum at 2phr.
[0130] 4) The addition of modified nano-SiO2 can improve the thermal stability of the CTPBA / EP resin system, and the glass transition temperature Tg decreases, but the loss factor tanδ and storage modulus E are higher than those of the pure CTPBA / EP resin matrix, and the damping temperature range is broadened, which is expected to develop in the damping field;
[0131] 5) The water absorption rate of nano-SiO2 modified CTPBA / EP shows a trend of first decreasing and then increasing with the increase of the amount of modified nano-SiO2 added, and reaches the minimum value when the addition amount is 2phr, at which time the water resistance is optimal.
[0132] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A nano-SiO2 / CTPBA / EP high-toughness adhesive, characterized in that: include: CTPBA / EP resin matrix, and nano-SiO2 modified by silane coupling agent and mixed therein.
2. According to claim 1, a nano-SiO2 / CTPBA / EP high-toughness adhesive, characterized in that: The dosage of nano-SiO2 is 1 to 5 phr.
3. A nano-SiO2 / CTPBA / EP high-toughness adhesive according to claim 2, characterized in that: The amount of CTPBA in the CTPBA / EP resin matrix is 20phr, and the amount of EP resin is 100phr.
4. The nano-SiO2 / CTPBA / EP high-toughness adhesive according to claim 1, characterized in that: The method of modifying nano-SiO2 with silane coupling agent is as follows: 1) Pretreatment: Place the nano-SiO2 in a 120°C oven for 1 day and then take it out for use; 2) Hydrolysis of silane coupling agent: Weigh 5% of the mass of nano-SiO2 silane coupling agent KH-550, add appropriate amount of deionized water to prepare a 5% aqueous solution, adjust the pH to 4-7, and place in an ultrasonic cleaning instrument for oscillation to fully hydrolyze the silane coupling agent; 3) Dispersing nano-SiO2: Adding nano-SiO2 into an ethanol solution to prepare an ethanol solution with a mass concentration of 5 wt.%, and placing it in an ultrasonic cleaning apparatus for oscillation to make the nano-SiO2 evenly mixed in the ethanol solution; 4) Modification of nano-SiO2: Add the hydrolyzed silane coupling agent solution to the nano-SiO2 / ethanol solution, place in a magnetic stirrer for modification, the temperature is 70°C, and the reaction is stopped after magnetic stirring for 2 hours; 5) Drying: Filter the modified nano-SiO2 and wash it with anhydrous ethanol to remove the residual silane coupling agent. Wash it several times, dry it in an oven at 120°C, and grind it to obtain the modified nano-SiO2.
5. A nano-SiO2 / CTPBA / EP high-toughness adhesive according to any one of claims 1 to 4, characterized in that: EP resin adopts bisphenol A epoxy resin with an epoxy value of 0.48 to 0.
52.
6. A nano-SiO2 / CTPBA / EP high-toughness adhesive according to any one of claims 1 to 5, characterized in that: Also includes: Curing agent, the amount of curing agent is 25phr.
7. The nano-SiO2 / CTPBA / EP high-toughness adhesive according to claim 6, characterized in that: The curing agent is phenolic amine T-31.
8. The nano-SiO2 / CTPBA / EP high-toughness adhesive according to claim 6, characterized in that: The preparation method is as follows: adding nano-SiO2 modified by silane coupling agent into CTPBA / EP resin matrix, stirring, ultrasonic vibration, adding curing agent, mixing and vacuum degassing.
9. The nano-SiO2 / CTPBA / EP high-toughness adhesive according to claim 8, characterized in that: The stirring time was 15 min and the ultrasonic shaking time was 30 min.
10. A nano-SiO2 / CTPBA / EP high-toughness adhesive as described in any one of claims 1 to 9, used for repairing seawater pipelines.